Modified recursive method to compute the multipath impulse response of the indoor wireless infrared channel - Supaat, Abu Sahmah; Mohammad, Abu Bakar; Kassim, Norazan; Janahiraman, Tiagrajah (2000)
The desire for an inexpensive and highspeed links has encouraged current research towards infrared frequency as a medium for indoor wireless communication. This paper presents a modified recursive algorithm to characterize the infrared propagation channel on multipath impulse response for indoor wireless communication. The mathematical model for the source, the receiver and the propagation channel were described. The results obtained were discussed and compared with other researchers.